PRAME-induced inhibition of retinoic acid receptor signaling-mediated differentiation: a possible target for ATRA response in AML without t(15;17) - Bullinger, Lars; Schlenk, Richard F.; Götz, Marlies; Botzenhardt, Ursula; Hofmann, Susanne; Russ, Annika C.; Babiak, Anna; Zhang, Lu; Schneider, Vanessa; Döhner, Konstanze; Schmitt, Michael; Döhner, Hartmut; et al. (Clinical cancer research, 2013)
Purpose: In acute myeloid leukemia (AML) without retinoic acid receptor (RAR) rearrangement, the effect of all-trans-retinoic acid (ATRA) is still poorly understood despite an association of NPM1 mutation and ATRA response. Recently, preferentially expressed antigen in melanoma (PRAME) has been shown to be a dominant repressor of RAR signaling. - Experimental Design: Thus, we further investigated ATRA response mechanisms, especially the impact of PRAME expression on ATRA responsiveness. We profiled gene expression in diagnostic samples derived from our AML HD98B trial, in which ATRA was administered in addition to intensive chemotherapy. - Results: Our data revealed a PRAME expression-associated gene pattern to be significantly enriched for genes involved in the retinoic acid metabolic process. In leukemia cell line models, we could show that retinoic acid-regulated cell proliferation and differentiation are impacted by PRAME expression. In patients with primary AML, repressor activity of high-PRAME levels might be overcome by the addition of ATRA as indicated by better outcome in 2 independent studies (P = 0.029). - Conclusions: PRAME seems to impair differentiation and to increase proliferation likely via blocking RAR signaling, which might be reversed by ATRA. PRAME therefore represents a promising target for both ATRA treatment and possibly future immunotherapeutic approaches in AML. Clin Cancer Res; 19(9); 2562-71. ©2013 AACR.
Gesehen am 03.12.2020